Drawn to the Screen by Who We Are and Who We Aspire to Be: Brand-Self Congruence Differences in Movie Preferences. Issue 3 (1st October 2020) - Kim, Danny D. E.
ABSTRACT: Established media preference theories implicitly presume that audiences know a media product's content or effects. Brands can fill this logical gap, with brands that media creators craft around their products providing cues about potential content or effects. Connecting parallel theories concerning self-congruence in communication and marketing research, this survey-based study examines whether individuals anthropomorphize movie product brands to have personalities and prefer those with personalities paralleling their own personality. In the process, it also introduces a novel "independent" congruence measure, where congruence is calculated between an individual's personality as they rate themselves and a movie's brand personality as rated by an independent sample. Results of paired t-tests and mixed ANCOVAs suggest that the previously unwatched movies individuals indicate being most likely to watch indeed have personalities more congruent to their own than do the previously unwatched movies individuals indicate being least likely to watch, while in terms of post-consumption evaluation, the movies that individuals indicated as their favorite tended to be less congruent with their personality than movies they indicated as their least favorite. Theoretical and practical ramifications are discussed.